DESIGN AND DEVELOPMENT OF PERSONNEL ADMINISTRATION SERVICE MONITORING APPLICATION BASED ON MOBILE HYBRID IN CIVIL SERVANTS AND HUMAN RESOURCES DEVELOPMENT, KAB. SUMENEP - Mohammad Andre Agazi; Vivine Nurcahyawati; Erwin Sutomo (Jurnal Sistem Informasi Universitas Dinamika, 2022)
BKPSDM is a regional apparatus work unit in charge of managing personnel management in Sumenep Regency. Personnel administration services are used to compile and manage daily service submissions so that all activities of employees can be fulfilled. There are 22 services that can be requested by employees. Based on the results of observations and interviews, there are several problems, namely the absence of monitoring from employees who apply for services so that these employees cannot find out information on services, besides that it can hamper the service process and abuse of authority. Another problem is that employees cannot know their personal data independently, quickly, and in real time. Based on these problems, BKPSDM needs an application that can monitor the personnel administration service process and personnel information data independently, quickly, and in real time. developed using hybrid mobile development (Flutter) technology so that it can be published on two Android and IOS operating systems, besides that it also uses realtime push notifications. With this application for monitoring personnel administration services, it can solve the above problems so that employees can find out information on the service process submitted in real time and also employees can know the data independently.